Bacteriological investigation of milk samples and biopsies from the mammary gland of healthy sows - Spiegel, Florian; Spiegel, Sebastian; von Altrock, Alexandra; Verspohl, Jutta; Seehusen, Frauke; Wendt, Michael (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2022)
Objective Milk samples from clinically healthy sows often contain a similar bacterial content as samples from mastitic sows. To verify whether contamination during sample collection is a possible reason for this or bacterial content in the mammary gland postpartum is a regular finding, the aim of the present study was to compare the suitability of milk samples and mammary gland biopsies for assessing the bacteriological status of healthy sows.Material and methods Twenty-five clinically healthy sows of different parities were selected. The mammary skin and teats were cleaned and disinfected before biopsies and milk samples were taken from the second mammary gland on the left udder side one day postpartum. Needle biopsies were performed after local anaesthesia. Samples were investigated bacteriologically for aerobic bacteria and a semi-quantitative classification of bacterial growth was carried out. Additionally, formalin-fixed paraffin-embedded biopsies from 18 of the healthy sows were stained and scored for inflammatory cells.Results A low bacterial content could be found in 96 % of milk samples and in 92 % of biopsies from the healthy sows. Both Gram-positive (mostly streptococci and staphylococci) and Gram-negative bacteria (Escherichia coli) were detected. Histopathological examination revealed mild inflammatory cell infiltration with mainly plasma cells and lymphocytes, in rare cases neutrophilic granulocytes.Conclusion Biopsies of the mammary gland provided similar results with regard to bacteriological investigation compared to milk sampling although these were collected under aseptic conditions. Therefore, it is assumed that ubiquitous bacteria are regularly present in the colostrum and in the mammary gland tissue of clinically healthy sows after parturition. Histopathological findings were not entirely uneventful.Clinical relevance Milk samples and biopsies from the thoroughly cleaned and disinfected mammary gland indicate a regular bacterial load of the gland postpartum; biopsies do not provide advantages with regard to hygienic conditions.
Keywords: swine; colostrum; needle biopsy; mastitis; histology